A Comparison of Antegrade Percutaneous and Laparoscopic Approaches in the Treatment of Proximal Ureteral Stones. (11th September 2014) - Topaloglu, Hikmet; Karakoyunlu, Nihat; Sari, Sercan; Ozok, Hakki Ugur; Sagnak, Levent; Ersoy, Hamit
Abstract : Purpose . To compare the effectiveness and safety of retroperitoneal laparoscopic ureterolithotomy (RLU) and percutaneous antegrade ureteroscopy (PAU) in which we use semirigid ureteroscopy in the treatment of proximal ureteral stones. Methods . Fifty-eight patients with large, impacted stones who had a history of failed shock wave lithotripsy (SWL) and, retrograde ureterorenoscopy (URS) were included in the study between April 2007 and April 2014. Thirty-seven PAU and twenty-one RLU procedures were applied. Stone-free rates, operation times, duration of hospital stay, and follow-up duration were analyzed. Results . Overall stone-free rate was 100% for both groups. There was no significant difference between both groups with respect to postoperative duration of hospital stay and urinary leakage of more than 2 days. PAU group had a greater amount of blood loss (mean hemoglobin drops for PAU group and RLU group were 1.6 ± 1.1 g/dL versus 0.5 ± 0.3 g/dL, resp.; P = 0.022 ). RLU group had longer operation time (for PAU group and RLU group 80.1 ± 44.6 min versus 102.1 ± 45.5 min, resp.; P = 0.039 ). Conclusions . Both PAU and RLU appear to be comparable in the treatment of proximal ureteral stones when the history is notable for a failed retrograde approach or SWL. The decision should be based on surgical expertise and availability of surgical equipment.